Mutations in encephalomyocarditis virus 3A protein uncouple the dependency of genome replication on host factors phosphatidylinositol 4-kinase IIIα and oxysterol-binding protein - Dorobantu, Cristina M.; Albulescu, Lucian; Lyoo, Heyrhyoung; Kampen, Mirjam van; Francesco, Raffaele De; Lohmann, Volker; Harak, Christian; Schaar, Hilde M. van der; Strating, Jeroen R. P. M.; Gorbalenya, Alexander E.; Kuppeveld, Frank J. M. van (mSphere, 2016)
Positive-strand RNA [(+)RNA] viruses are true masters of reprogramming host lipid trafficking and synthesis to support virus genome replication. Via their membrane-associated 3A protein, picornaviruses of the genus Enterovirus (e.g., poliovirus, coxsackievirus, and rhinovirus) subvert Golgi complex-localized phosphatidylinositol 4-kinase IIIβ (PI4KB) to generate “replication organelles” (ROs) enriched in phosphatidylinositol 4-phosphate (PI4P). PI4P lipids serve to accumulate oxysterol-binding protein (OSBP), which subsequently transfers cholesterol to the ROs in a PI4P-dependent manner. Single-point mutations in 3A render enteroviruses resistant to both PI4KB and OSBP inhibition, indicating coupled dependency on these host factors. Recently, we showed that encephalomyocarditis virus (EMCV), a picornavirus that belongs to the Cardiovirus genus, also builds PI4P/cholesterol-enriched ROs. Like the hepatitis C virus (HCV) of the Flaviviridae family, it does so by hijacking the endoplasmic reticulum (ER)-localized phosphatidylinositol 4-kinase IIIα (PI4KA). Here we provide genetic evidence for the critical involvement of EMCV protein 3A in this process. Using a genetic screening approach, we selected EMCV mutants with single amino acid substitutions in 3A, which rescued RNA virus replication upon small interfering RNA (siRNA) knockdown or pharmacological inhibition of PI4KA. In the presence of PI4KA inhibitors, the mutants no longer induced PI4P, OSBP, or cholesterol accumulation at ROs, which aggregated into large cytoplasmic clusters. In contrast to the enterovirus escape mutants, we observed little if any cross-resistance of EMCV mutants to OSBP inhibitors, indicating an uncoupled level of dependency of their RNA replication on PI4KA and OSBP activities. This report may contribute to a better understanding of the roles of PI4KA and OSBP in membrane modifications induced by (+)RNA viruses. - IMPORTANCE Positive-strand RNA viruses modulate lipid homeostasis to generate unique, membranous “replication organelles” (ROs) where viral genome replication takes place. Hepatitis C virus, encephalomyocarditis virus (EMCV), and enteroviruses have convergently evolved to hijack host phosphatidylinositol 4-kinases (PI4Ks), which produce PI4P lipids, to recruit oxysterol-binding protein (OSBP), a PI4P-binding protein that shuttles cholesterol to ROs. Consistent with the proposed coupling between PI4K and OSBP, enterovirus mutants resistant to PI4KB inhibitors are also resistant to OSBP inhibitors. Here, we show that EMCV can replicate without accumulating PI4P/cholesterol at ROs, by acquiring point mutations in nonstructural protein 3A. Remarkably, the mutations conferred resistance to PI4K but not OSBP inhibitors, thereby uncoupling the levels of dependency of EMCV RNA replication on PI4K and OSBP. This work may contribute to a deeper understanding of the roles of PI4K/PI4P and OSBP/cholesterol in membrane modifications induced by positive-strand RNA viruses.